2019
DOI: 10.2147/ppa.s192008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of patient education on medication adherence of patients with rheumatoid arthritis: a randomized controlled trial

Abstract: PurposeThere is a general understanding that patient educational interventions for enhancing medication adherence are important. However, their success at improving adherence is debatable. This study aimed to assess the influence of different modes of patient education on medication adherence in patients with rheumatoid arthritis (RA).Materials and methodsOne hundred and twenty RA patients with non-adherence, defined as pill count ≥80% or medication-taking behavior questionnaire for Thai patient ≥23, were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
1
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 56 publications
4
45
1
4
Order By: Relevance
“…During discussion, the importance of shared decision-making was reiterated and the importance of patient education emphasised. Indeed, patient education may increase adherence to medication49; moreover, education of rheumatologists may foster adherence to appropriate assessment strategies 50. There were suggestions made to expand this item by mentioning the importance of patient education separately, but there was ultimate agreement that patient education forms the implicit and inseparable basis for shared decision-making.…”
Section: Resultsmentioning
confidence: 99%
“…During discussion, the importance of shared decision-making was reiterated and the importance of patient education emphasised. Indeed, patient education may increase adherence to medication49; moreover, education of rheumatologists may foster adherence to appropriate assessment strategies 50. There were suggestions made to expand this item by mentioning the importance of patient education separately, but there was ultimate agreement that patient education forms the implicit and inseparable basis for shared decision-making.…”
Section: Resultsmentioning
confidence: 99%
“…This is in line with previous research which showed the significant relationship between formal education and medication adherence. 48,49 The number of medications had a significant correlation with medication adherence. Medication adherence increases when the patient is using more than one medication to control blood pressure.…”
Section: Discussionmentioning
confidence: 97%
“…Pharmacists routinely provide patients with information sheets that contain an exhaustive review of side effects of HU and special handling instructions, given that HU is classified as a cytotoxic drug . Although limited data exist regarding the sources of information that pediatric patients with SCD and their families use to inform their decision‐making surrounding medication acceptance, previous studies have found a positive association between accurate patient education about therapy and adherence . Written information materials in particular have been shown to contribute to patient decision‐making regarding therapy initiation in several other disease states and serve as an influential adjunct to patient counseling.…”
Section: Introductionmentioning
confidence: 99%
“…20 Although limited data exist regarding the sources of information that pediatric patients with SCD and their families use to inform their decision-making surrounding medication acceptance, previous studies have found a positive association between accurate patient education about therapy and adherence. 15,21 Written information materials in particular have been shown to contribute to patient decision-making regarding therapy initiation in several other disease states [22][23][24] and serve as an influential adjunct to patient counseling. Therefore, the goal of this study was to evaluate the written material provided to patients with SCD by pharmacies to gain a better understanding of the information available to patients and to compare this information to a reference standard HU patient information handout (PIH) for patients with SCD.…”
mentioning
confidence: 99%